Use of flux balance analysis and metabolomics in the analysis of the respiratory pathway in saccharomyces cerevisiae - Dikicioğlu, Duygu. (Thesis (M.S)-Bogazici University.Institute for Graduate Studies in Science and Engineering, 2005., 2005)
BY4743 and the mutants ?HO, ?QDR3, ?MIG1, ?HAP4, ?QCR7, ?RIP1 and ?CYT1 of S. cerevisiae are investigated to improve knowledge on the regulatory mechanism of respiratory chain and construction of a high ethanol production strain. Cells were grown in rich medium in batch and continuous cultivations and BY4743 was also cultivated under nutritional stress and relaxed conditions. In batch cultivations, ?QDR3 had overgrown BY4743 and highest ethanol producing strain was ?QCR7. In continuous cultivation, highest amount of biomass was produced by BY4743 whereas the lowest levels of biomass by ?RIP1, ?HAP4 and ?CYT1. ?RIP1 has lowest glucose consumption and highest ethanol production. Metabolic modeling of yeast cells revealed that when the appropriate objective function is used, computed results are in agreement with the experimental values. MOMA analysis indicated ?HO and ?QDR3 to be metabolically more adjusted to the wild type. PCA revealed that the deletion strains resulting in similar deficiencies were found to be clustered together. Gene expression analysis for HAP4 gene performed on the parental strain showed declining expression levels as response to glucose repression in carbon limitation and increase in expression levels due to its regulatory function on the ammonia metabolism in nitrogen catabolite repression in nitrogen limitation.
Keywords: Saccharomyces cerevisiae.; Gene expression.; Alcohol.; Molecular genetics.